Prediction analysis of shield vertical attitude based on GRU. (November 2020) - Li, Liang; Hu, Changming; Hou, Yajun
Abstract: To solve the active control of the shield vertical attitude, this paper established the GRU model to realize the prediction of the pitch angle, which can reflect the shield vertical attitude. Firstly, the tunneling parameters, geological parameters and geometric parameters were selected as the influencing factors sets, and a series of data pre-processing strategies were established. And then, the GRU model was established, mainly including the division of training data, the optimization of hyperparameters, the determination of the objective function and optimization algorithm. Eventually, the shield interval from Chengdu was used to verify the new model. As a result, compared with the BP model and LSTM model, it could be found that the MGRU model had higher accuracy. This study could provide references for the prediction and help the engineers to realize the active control in the field of the shield attitude.